2015
DOI: 10.1371/journal.ppat.1004712
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Intracellular and Exosomal microRNAs on Viral E6/E7 Oncogene Expression in HPV-positive Tumor Cells

Abstract: Specific types of human papillomaviruses (HPVs) cause cervical cancer. Cervical cancers exhibit aberrant cellular microRNA (miRNA) expression patterns. By genome-wide analyses, we investigate whether the intracellular and exosomal miRNA compositions of HPV-positive cancer cells are dependent on endogenous E6/E7 oncogene expression. Deep sequencing studies combined with qRT-PCR analyses show that E6/E7 silencing significantly affects ten of the 52 most abundant intracellular miRNAs in HPV18-positive HeLa cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
217
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(233 citation statements)
references
References 132 publications
12
217
0
4
Order By: Relevance
“…Honegger et al determined how the intracellular and exosomal miR pool in HPVpositive tumor cells is affected by sustained expression of the viral E6/E7 oncogenes. RNA deep sequencing analysis showed abundance of pro-tumorigenic miRs such as miR-7-5p and miR-378a-3p in exosomes from cells expressing high levels E6/E7, further supporting the significant role of oncogenes in promoting miR loading onto exosomes [47]. Shen et al showed that epidermal growth factor receptor (EGFR), a known oncogene in several cancers, suppresses maturation of several tumor suppressor miRs under hypoxic conditions by phosphorylating Ago2 [48].…”
Section: Mir-selective Sorting Mechanisms In Exosomesmentioning
confidence: 94%
“…Honegger et al determined how the intracellular and exosomal miR pool in HPVpositive tumor cells is affected by sustained expression of the viral E6/E7 oncogenes. RNA deep sequencing analysis showed abundance of pro-tumorigenic miRs such as miR-7-5p and miR-378a-3p in exosomes from cells expressing high levels E6/E7, further supporting the significant role of oncogenes in promoting miR loading onto exosomes [47]. Shen et al showed that epidermal growth factor receptor (EGFR), a known oncogene in several cancers, suppresses maturation of several tumor suppressor miRs under hypoxic conditions by phosphorylating Ago2 [48].…”
Section: Mir-selective Sorting Mechanisms In Exosomesmentioning
confidence: 94%
“…miR-143 expression has been reported to be downregulated in human cervical cancer tissues (13). Furthermore, previous studies have revealed that miR-143 is downregulated in HPV-induced pre-neoplastic lesions, which suggests that miR-143 may have a significant role in the early stages of cervical cancer development (13,14).…”
Section: Introductionmentioning
confidence: 98%
“…miRs are able to regulate multiple target genes simultaneously (15). miR-143 has been demonstrated to target Kirsten rat sarcoma viral oncogene homolog (KRAS) (16), matrix metalloproteinase-13 (7), epithelial-mesenchymal transition (17), cyclooxygenase-2 (6) and cluster of differentiation 44v3 (3), and is able to suppress cell growth and metastasis in vitro and in vivo in several types of tumor (13). Among the target genes regulated by miR-143, in silico screening of gene targets for miR-143 was performed using TargetScan (www.targetscan.org).…”
Section: Introductionmentioning
confidence: 99%
“…HPVs16 and HPVs18 are the most common forms of cervical cancers in HPVs types around the world, which were found about 50% and 20% of the cases, respectively [6,7]. However, the E6 and E7 proteins of high-risk HPVs determines the behavior of deteriorating development to the potential host cells [8][9][10]. The deteriorative E6 oncogene is commonly accepted to determine the tumorigenic character of HPVs positive cancer cells [11].…”
Section: Introductionmentioning
confidence: 99%